The Illusion of Risk Control: What Does it Take to Live With Uncertainty? - Motet, Gilles; Bieder, Corinne (SpringerBriefs in Applied Sciences and Technology, 2017)
risk management; black swans; safety; high-risk organisations; FonCSI; complexity in risk management; risk assessment